The Evaluation of Electronic Procurement Implementation at Social and Political Sciences Faculty of Brawijaya University as an effort to achieve Good Governance - Pradana, Adi Hidayat; Ghofar, Abdul (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study aims to evaluate the implementation of E-procurement in the Faculty of Social and Political Sciences UB whether it has met the standards of transparency and accountability based on the theory of Good Governance put forward by the United Nations Development Program (UNDP). This research uses descriptive qualitative research approach. Respondent in this study is the auction officials and service users. The results of this study indicate that the E-procurement is implemented in the Faculty of Social UB meets the standards of Good Governance according to the theory of UNDP, particulary the element of transparency and accountability has been well implemented. From this study it is found that the transparency and accountability within the Faculty of Social UB has been implemented well and it has fullfiled the criteria of Good Governance as well as the law. It can be concluded that the Faculty of Social UB has implemented E-procurement satisfactorily and in accordance with the law.Keywords: Good Governance, E-procurement, Procurement of Goods and Services